Pediatric TSH Reference Intervals and Prevalence of High Thyroid Antibodies in the Lebanese Population - Marie-Hélène Gannagé-Yared; Nicole Balech; Vanessa Farah; Marianne Antar; Rindala Saliba; Elise Chahine (International Journal of Endocrinology, 2017)
The aims of this study are to establish reference values for TSH in Lebanese schoolchildren; to look at the relationship between TSH and age, gender, BMI, socioeconomic status (SES), and thyroid antibodies (TAb); and to investigate the prevalence of abnormal TAb in this population. 974 Lebanese schoolchildren aged 8–18 years were recruited from 10 schools of different SES. Third-generation TSH, TPO-Ab, and Tg-Ab measurements were performed using the IMMULITE chemiluminescent immunoassay. The mean TSH is 2.06±1.05 μUI/ml. TSH values are inversely correlated with age p<0.0001, are higher in boys than in girls (resp., 2.14±1.10 and 1.98±0.99 μUI/ml, p=0.017), and are positively correlated with BMI p<0.0001. They are also significantly higher in subjects from low-SES schools p=0.03 and in girls with positive TAb p=0.026. In boys, TSH is independently associated with age, BMI, and schools’ SES (p=0.01, p=0.03, and p=0.026, resp.) while in girls, the association is only significant for age and TAb (p=0.0001 and p=0.015, resp.). The prevalence of TAb is 4.3% (3% for TPO-Ab and 2.1% for Tg-Ab). Our results showed higher TSH values in the pediatric Lebanese population compared to western populations. TSH varies according to age, gender, BMI, and SES and is associated in girls with TAb.